A Multi-Method Approach to Assessing Teacher Satisfaction Regarding the Ruang GTK Platform: A Study Using the EGOVQUAL Method, Importance-Performance Analysis, Customer Satisfaction Index, and Technology Acceptance Model - Siti Sholihah Ari Susanti; Eka Ardhianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aimed to eval__uate the level of teacher satisfaction regarding the Ruang GTK digital service by integrating four analytical approaches, namely Electronic Government Quality (EGOVQUAL), Importance-Performance Analysis (IPA), Customer Satisfaction Index (CSI), and the Technology Acceptance Model (TAM). EGOVQUAL was used to assess the quality of digital government services based on public service dimensions, while IPA mapped the importance and performance levels of service attributes. CSI was used to quantitatively measure the level of satisfaction, and TAM was used to examine the effect of perceived usefulness and ease of use on teachers’ intention to continue using the Ruang GTK platform. This study used a quantitative method by distributing questionnaires to teachers who use the Ruang GTK platform. The results of the study showed that, in general, Ruang GTK provides a satisfactory service. However, several service attributes need to be prioritized for improvement based on the results of the IPA analysis. The CSI score placed this service in the “satisfied” category. In addition, the TAM analysis indicated that perceived usefulness and ease of use had a significant effect on teachers’ intention to continue using the platform. This study contributes to efforts to improve the quality of digital government services in the education sector, particularly in supporting the role of educators